Impact of Pathology Review in Adverse Histological Characteristics and pT Stages of Upper Tract Urothelial Cancer in a Multicenter Study - Chang, Chia-Hui; Wu, Wen-Jeng; Lee, Hsiang-Ying; Lin, Chih-Hung; Yue, Chung-Tai; Jiang, Yuan-Hong; Lee, Yu-Khun; Huang, Kuan Hsun; Tsai, Yao Chou (Frontiers in Oncology, 2021)
Purpose: Pathology review for upper urinary tract cancer (UTUC) remained scarce in the literature. Here, we reported the inter-observer variation among the review and local pathology for featured histologic characteristics for UTUC. Methods: Patients who underwent definitive surgical treatments for UTUC were retrospectively reviewed for eligibility for pathology review. In Taiwan UTUC Collaboration cohort, 212 cases were reviewed, of which 154 cases were eligible for pathology review. Agreement between original pathology and review pathology was measured by the total percentage of agreement and by simple kappa statistics. The prognostic impact was analyzed by the Cox regression model with the estimation of hazard ratios (HR) and 95% confidence intervals. Results: There were 80 women and 74 men enrolled in this study and the median age at treatment was 71.7 years. The agreement is moderate agreement for surgical margin status (87.7%; κ=0.61), tumor grade (82.5%; κ=0.43), tumor invasiveness (76.6%; κ=0.45), lymphovascular invasion (70.8%; κ=0.42) and T stage (67.5%; κ=0.52). The interobserver agreement for perineural invasion and variant histology identification were slight. Kaplan Meier analysis for disease free survival revealed comparable results in local and review pathology for localized (Tis, Ta, T1-2) or advanced T stage (T3-4). Conclusions: Pathology review of UTUC had minimal impact on clinical practice based on current available disease treatment guidelines. However, significant interobserver variations were observed in featured adverse histopathological characters.